PENGARUH KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KECAMATAN (Studi Kasus pada Pegawai Kantor Kecamatan Cipari dan Pegawai Kantor Kecamatan Kedungreja) - Prasetyo, Fakhri Bari; Werdiasih, Rustina Dewi; S, Sudiyono (JURNAL EKONOMI, 2025)
This research aims to determine the influence of leadership, motivation and work environment on the performance of sub-district employees. The method used in this research uses quantitative methods and the sample used in this research was 31 respondents. Data collection method using questionnaires. Data analysis used multiple regression analysis. The results of the research show that in the F regression test carried out it was found that all variables including leadership, motivation and work environment simultaneously influenced the performance of sub-district employees. This is indicated by the F test value which produced a calculated F value of 10.325 which is greater than F table 2. 96. Based on the results of the T test carried out partially, the variables that influence employee performance are leadership. This is indicated by the calculated T value of 2.771, while the motivation variable is 1.727 and the work environment is 1.270, which partially has no effect on employee performance.